Analysis of effective properties of materials by using the boundary element method - Fedeliński, P.; Górski, G.; Czyż, T.; Dziatkiewicz, G.; Ptaszny, J. (Archives of Mechanics, 2014)
In this work different formulations of the boundary element method (BEM) in an analysis of materials with inclusions are presented. Models of composites in the form of linear-elastic solids containing rigid inclusions, elasto-plastic composites and piezomagnetic composites are considered. It is assumed that perfectly bonded matrix and inclusions are made of homogeneous materials. The developed computer codes are used to compute effective material properties by considering unit cells or representative volume elements (RVE). The influence of volume fractions of inclusions on overall properties of materials is studied.